An observational study of clinical profile and outcome of syphilis infection during pregnancy in the tertiary care center - Gangwar, Pooja; Jhinwal, Arti; Gupta, Preksha; Dixit, Eshu; Bajaj, Suchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Syphilis is a sexually transmitted disease (STD) caused by the bacterium treponema pallidum, but little is known about its mechanism of action. In pregnancy it leads to adverse outcomes among more than half of the women with active disease, including early fetal loss, stillbirth, prematurity, low birth weight, neonatal and infant death. Methods: It is an observational study in the department of obstetrics and gynecology Mahatma Gandhi Memorial Medical College Maharaja Yashwant Rao Hospital, Indore between January 2014 to December 2015 total 20870. In Include written informed consent, All the patients attending STI/RTI clinic with clinical diagnosis of STD. In Exclusion criteria include patients not give informed consent. Case definition: All VDRL + TPHA positive patients. Results: Out of 20870 females on which VDRL was performed 77 (0.036%) were found to be positive. The seroprevalence at study hospital thus came out to be 0.036%. These were further confirmed by TPHA and 73 (94.8%) out of 77 samples were positive. A total agreement was seen between TPHA and VDRL with a titer of 1 in 8 and above. Among total 20870 screened females, 77% (16101) were ANC patients of which 26 cases out of 77 that is 33.76% females were syphilis positive. Conclusions: Low prevalence of syphilis in pregnant women and adult general population is very encouraging. participation of people and public health approach to promote awareness of syphilis among physicians and populations at risk in India are very urgently needed to avoid the adverse consequences which could result from undiagnosed or improper treatment.